Practical Experiences of Unsuccessful Hemostasis with Covered Self-Expandable Metal Stent Placement for Post-Endoscopic Sphincterotomy Bleeding - Michihiro Yoshida; Tadahisa Inoue; Itaru Naitoh; Kazuki Hayashi; Yasuki Hori; Makoto Natsume; Naoki Atsuta; Hiromi Kataoka (Korean Society of Gastrointestinal Endoscopy, 2022)
We reviewed 7 patients with unsuccessful endoscopic hemostasis using covered self-expandable metal stent (CSEMS) placement for post-endoscopic sphincterotomy (ES) bleeding. ES with a medium incision was performed in 6 and with a large incision in 1 patient. All but 1 of them (86%) showed delayed bleeding, warranting second endoscopic therapies followed by CSEMS placement 1-5 days after the initial ES. Subsequent CSEMS placement did not achieve complete hemostasis in any of the patients. Lateral-side incision lines (3 or 9 o'clock) had more frequent bleeding points (71%) than oral-side incision lines (11-12 o'clock; 29%). Additional endoscopic hemostatic procedures with hemostatic forceps, hypertonic saline epinephrine, or hemoclip achieved excellent hemostasis, resulting in complete hemostasis in all patients. These experiences provide an alert: CSEMS placement is not an ultimate treatment for post-ES bleeding, despite its effectiveness. The lateral-side of the incision line, as well as the oral-most side, should be carefully examined for bleeding points, even after the CSEMS placement.